Stella Maris [large type] - McCarthy, Cormac, 1933- (Passenger, 2022)
The best-selling, Pulitzer Prize-winning author of The Road returns with the second volume of The Passenger series: Stella Maris is an intimate portrait of grief and longing, as a young woman in a psychiatric facility seeks to understand her own existence. 1972, BLACK RIVER FALLS, WISCONSIN: Alicia Western, twenty years old, with forty thousand dollars in a plastic bag, admits herself to the hospital. A doctoral candidate in mathematics at the University of Chicago, Alicia has been diagnosed with paranoid schizophrenia, and she does not want to talk about her brother, Bobby. Instead, she contemplates the nature of madness, the human insistence on one common experience of the world; she recalls a childhood where, by the age of seven, her own grandmother feared for her; she surveys the intersection of physics and philosophy; and she introduces her cohorts, her chimeras, the hallucinations that only she can see. All the while, she grieves for Bobby, not quite dead, not quite hers. Told entirely through the transcripts of Alicia's psychiatric sessions, Stella Maris is a searching, rigorous, intellectually challenging coda to The Passenger, a philosophical inquiry that questions our notions of God, truth, and existence.--